O que amamos, não esquecemos: um estudo teológico, identitário e cultural dos cemitérios teutos no sul do Brasil - Araújo, Thiago Nicolau de (2015)
The dissertation proposes to analyze the cemetery as a space of expression and preservation of the German identity memory in southern Brazil, through the interpretation of religious symbolic elements contained on the tombstones as well as of their spatial and organizational structure. The research was built on extensive bibliographic review and on field research of the cemeteries localized in communities of German origin in Rio Grande do Sul and in the cemeteries of Germany. The first chapter occupies itself with the definition of tomb as well as with the relation of the individual with finitude and its funerary representations. The second chapter presents the cemetery as a place of memory and identity, through the study of sources of artistic, social, cultural and ideological information contained in these so as to identify the construction of one or more cultural identities. The third chapter establishes a theoretical framework about the construction of the European imagery about death and cemeteries and in what way this is represented materially on the tombs, analyzing the Catholic and Protestant religious characteristics expressed in cemetery symbology between 1824, the beginning of the German immigration to Brazil, up to 1930, the period which marks the end of these trans-cultural expressions on the tombs. Finally, the last chapter establishes a comparative study between the cemeteries of the German immigrants in southern Brazil and the cemeteries of their country of origin, Germany, seeking to define which symbolic elements reveal the maintenance of a German religious identity expressed in the symbols and in the epitaphs so as to analyze the construction of one or more cultural identities preserved in the German cemeteries of Rio Grande do Sul.